Effect of Transient Feed Withdrawal Stress on Physiological Indices and Acid-Base Balance in Equid - Pal, Yash; Gupta, A K (Annals of Arid Zone, 2016)
Impact of transient feed withdrawal was conducted on physiological responses.blood gases and acid-base balance was studied on indigenous donkeys and mules.The transient wi thdrawal of feed leading to starvation for 10 successi ve days progressi vel yreduced the total water intake almost to a similar extent both in donkeys andmules. Comparatively little or no effect on rectal temperature and pulse rate duringstarvation stress in donkeys as compared to the significant effect observed in mules,reflected a better tolerance of donkeys over mules under total feed withdrawalstress. The values of pCOz and pH in blood decreased significantly (P